Data Analysis of Home Visits by Posyandu Cadres at Ministry of Health Republic Indonesia in 2024 - Putri Ansyari, Alya; Rohmah, Nur; Diah, Ni Made (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : The Ministry of Health Republic Indonesia has initiated a transformation in the health sector, one of which is through strengthening primary health services. To reach all families in the community, posyandu cadres are empowered to carry out home visits. Objective : To determine the percentage of home visits that have been carried out by posyandu cadres nationally. Research Methods/ Implementation Methods : The methods include interviews with Tim Kerja Pemberdayaan Masyarakat di Pustu dan Posyandu Kemenkes RI, as well as structured participatory observation by following the daily activities of the work team and based on the results of the literature study Results : Based on data sourced from the Microsite Promkes and PM as of September 4, 2024. The national target families that have been inputted are 17,489,481, but the data does not reflect the actual number because it has not been fully inputted and it is estimated that the total families in Indonesia are estimated to be more than 80 million families. So far, cadres have visited 5,518,726 families with a national achievement of 32 percent. Of course, continuous evaluation and monitoring is needed to complete these data in order to improve the health status of the community and provide an overview of the implementation of clean and healthy living behaviors. Conclusion/Lesson Learned : Home visits conducted by cadres are part of the primary health transformation initiated by the Ministry of Health Republic Indonesia. The percentage of home visits nationally has reached 32 percent. Of course, continuous monitoring and evaluation is needed to complete the data so that it can improve public health status and provide an overview of clean and healthy living behavior in the community.